POPULASI dan PERSENTASE SERANGAN LARVA Spodoptera spp. (LEPIDOPTERA: NOCTUIDAE) pada TANAMAN BAWANG DAUN di KECAMATAN MODOINDING - Arter G. Umboh; Dantje Tarore; Moulwy Dien (COCOS, 2017)
ABSTRACT The study aims to determine the percentage of the population and attacks the larvae of Spodoptera spp. the planting scallion in District Modoinding. The study used survey method in planting scallion in District Modoinding, South Minahasa Regency is in the village Mokobang, Makaaruyen, Palelon and Kakenturan. Each location / Village determined three terraced planting scallion as sample sites. Sampling was done by slices diagonally and consists of five sub-plots. Observations made by observing the plant population of 20 clumps on each sub-plot. Larvae were found taken and collected in a bottle collection that already contains 70% alcohol, then calculated the amount. Sampling was carried out four times with intervals of once a week, namely the old plants 30 days after planting (dap), 37 dap, 44 dap and 51 dap. Observations made once the percentage of attacks that the old plants 51 days after planting. Each sub-plots randomly selected 20 family of plants as the plant sample to be observed. So the number of samples of plants were observed in each plot were 100 plants. Each family of plants counted the number of leaves, then observe and note the number of the diseased leaf. Criteria of pest attack is characterized by the presence of symptoms or attacks and the presence of larvae of Spodoptera spp. the leaves were observed Results of the study was a population of larvae of Spodoptera spp. The highest was found in the village of Mokobang reached an average of 88,31, then Makaaruyen 52,33, 51,48 Palelon village head and village Kakenturan 7,50. The observation of the population of Spodoptera spp. based on the age of the plant turned out to be the highest found in the plant was 51 dap which reached 67,37 then aged 44 dap 51,15, age 37 dap 43,75 and age 30 dap 37,56. Observations percentage of attacks Spodoptera spp. turned out to be the highest in location the Mokobang vilage reaching 41,42%, Palelon Village 11,68 %, Makaaruyen village 11,37 % and Kakenturan village 2,74 %.